Creating Educational Trifold Brochures from Microsoft Word® Templates: An Example from the Florida Master Naturalist Program - Martin B. Main; Ginger M. Allen (EDIS)
WEC204, a 3-page fact sheet by Martin B. Main and Ginger M. Allen, provides tips and guidelines for developing a trifold brochure and includes a Microsoft Word template that can be copied and easily modified to present the reader a message. Published by the UF Department of Wildlife Ecology and Conservation, July 2006.